EPISTIMOLOGI ILMU PENGETAHUAN - Raisha Khotimah (PT. Hasba Edukasi Mandiri, 2025)
This article discusses epistemology as one of the main branches of the philosophy of science that focuses on the nature, sources, methods, and validity of knowledge. Epistemology plays a crucial role in the development of science because it provides a philosophical basis for how knowledge is acquired and its truth is validated. This research uses a library research approach by examining various classical and contemporary literature related to epistemology. The results of the discussion indicate that epistemology encompasses the study of sources of knowledge such as the senses, reason, and intuition, the scope of epistemology which includes science, gnosis, and knowledge, as well as various epistemological schools of thought such as rationalism, empiricism, criticism, realism, and idealism. Understanding epistemology is crucial for developing critical and systematic thinking, particularly in the development of science and education.